Effects of an in situ diesel oil spill on oxidative stress in the clam Anomalocardia flexuosa. (November 2017) - Sardi, Adriana E.; Renaud, Paul E.; Morais, Gisele C.; Martins, César C.; da Cunha Lana, Paulo; Camus, Lionel
Abstract: Intensive exploitation and transport of oil and derivatives are increasing the risk of coastal contamination by either dramatic disasters or diffuse sources. Tools for monitoring diffuse contamination, such as diesel oil that leaks from marine vessels are much needed. We experimentally tested the efficiency of antioxidant biomarkers as indicators of chronic exposure to diesel oil in a mudflat from the subtropical Bay of Paranaguá, in southern Brazil. We examined the effects of three successive diesel oil spills, with two weeks of recovery time between exposures, on the edible clam Anomalocardia flexuosa . Previous studies have highlighted its potential as a bioindicator species for diesel oil contamination in subtropical and tropical ecosystems. Endpoints measured in gill and digestive gland homogenates included the activity of antioxidant enzymes SOD, GPx, GST and levels of lipid peroxides. PAHs concentration in sediments and soft tissue were also quantified. GST and SOD were the most responsive biomarkers to the exposure. There were significant but non–cumulative departures from control levels in organisms from treated samples, which were, in all cases, more common 48 h after each experimental spill. Biomarker responses were more evident in the digestive gland than in gills. This work validated the short–term responsiveness of biomarkers as measures of repeated pulsed in situ exposure to low concentrations of diesel oil. For their routine implementation into monitoring programs for tropical estuaries our general recommendations are 1) to include several reference sites, 2) to analyze biomarker data using a logarithmic–scale and 3) to interpret deviations from "normal" activity as multiplicative interval differences. Graphical abstract: Highlights: Effects of repeated diesel spills on antioxidant biomarkers in situ were investigated during 5-weeks. Significant departures from control levels were more common 48 h after each experimental spill. Biomarkers' response was non–cumulative. SOD and GST activities reflected the exposure to low concentrations of diesel oil. Biomarkers' natural variability was "extracted" by using logarithmic response ratios. Abstract : The effect of low concentration diesel oil spills was detectable by measuring the activity of antioxidant enzymes in the clam Anomalocardia flexuosa exposed in situ conditions.